Discovering dad: paternal roles, responsibilities, and support needs as defined by fathers of children with complex cardiac conditions perioperatively. (8th August 2019) - Robinson, Jacob; Huskey, David; Schalley, Sabrina; Wratchford, Dale; Hammel, James; Weaver, Meaghann S.
Abstract: Background: Understanding perceptions of family caregivers' roles and responsibilities regarding their child with complex cardiac needs has potential to help care teams better support parents. Paternal experience has been under-explored in pediatric cardiac cohorts. Methods: Ten fathers of children undergoing cardiac surgery completed quantitative surveys on their knowledge needs and preferred format of communication. In face-to-face recorded interviews, they responded to open-ended questions about the definition of being a good father to a child with a complex cardiac condition, perceived paternal responsibilities, personal growth as a parent to a child with a complex heart condition, support needs, and recommendations to medical staff for paternal inclusion. Semantic content analysis was utilised. The study reports strictly followed COnsolidated criteria for REporting Qualitative research guidelines. Results: The fathers reported high preference for knowledge about the child's heart condition, communication about the treatment plan, and desire for inclusion in the care of their child. Paternal role was defined thematically as: providing a supportive presence, being there, offering bonded insight, serving as strong provider, and acting as an informed advocate. The fathers revealed that their responsibilities sometimes conflicted as they strove to serve as an emotional and economic stabiliser for their family, while also wanting to be foundationally present for their child perioperatively. Conclusion: This study provides insight into paternal experience and strategies for paternal inclusion. This summary of the self-defined experience of the fathers of pediatric cardiac patients offers constructive and specific advice for medical teams.